Understanding LKS Financing Products Based on Salam Sale and Purchase at BMT NU East Java Burnih - Husnus Shawab (Al-Abqori: Journal of Islamic Thought Studies, 2025)
This study explores the operational strategies and performance of Baitul Maal wat Tamwil Nahdlatul Ulama (BMT NU) in East Java, Indonesia. BMT NU, as a microfinance institution grounded in Islamic principles, aims to empower economically underserved communities while adhering to Sharia law. The research examines its role in promoting financial inclusion, reducing poverty, and fostering economic growth in rural and urban areas of East Java. Key aspects investigated include the governance framework, funding mechanisms, and the integration of social and economic objectives. The findings highlight the effectiveness of BMT NU's dual function as a financial intermediary and a socio-economic development agent. Its ability to provide affordable credit, encourage savings, and distribute zakat has significantly impacted the socio-economic welfare of its members. Challenges such as regulatory compliance, market competition, and technological adaptation are also discussed. Recommendations are provided to enhance BMT NU's sustainability and scalability in addressing the diverse needs of East Java's communities. This study contributes to the understanding of Islamic microfinance's potential in achieving inclusive economic development.